GREENING THE NETWORKS: A COMPARATIVE ANALYSIS OF DIFFERENT ENERGY EFFICIENT TECHNIQUES - Arshad, M. J.; Saeed, Sameen S.; Javed, M.; Durrani, A. I. (The Nucleus, 2014)
From a room electric bulb to the gigantic backbone networks energy savings have now become a matter of considerable concern. Issues such as resource depletion, global warming, high energy consumptions and environmental threats gave birth to the idea of green networking. Serious efforts have been done in this regard on large scale in the ICT sector. In this work first we give an idea of how and why this modern technology emerged. We then formulate a precise definition of the term green technology. We then discuss some leading techniques which are promising to produce â€œgreen-resultsâ€ when implemented on real time network systems. These technologies are viewed from different perspectives e.g. hardware implementations, software mechanisms and protocol changingâ€™s etc. We then compare these techniques based on some pivotal points. The main conclusion is that a detailed comparison is needed for selecting a technology to implement on a network system.